GRINDING BALLS WITH PARTICULAR ACCURACY - V. Yu. Rubtsov; O. I. Shevchenko; P. A. Alypov; V. A. Lebedev (Известия высших учебных заведений. Поволжский регион:Технические науки, 2020)
Backgrounds. It is possible to obtain grinding balls production by cross-helical rolling method, with particular accuracy to their geometry. It is relevant to divide produced grinding balls nomenclature into 2 groups of geometric accuracy. It is recomend use of “particular accuracy” to balls intended for heat treatment into the fifth hardness grade. The study object is grinding balls. The research subject is process of grinding balls production on modern equipment with high geometric parameters achievement. The aim of this resurche is it structure the parameters to which accuracy of the grinding balls geometric dimensions on, determining their influence degree, as well as the maximum deviations for proposed group of high accuracy balls. Materials and methods. The study was carried out in conditions of the EVRAZNTMK JSC rail and beam workshop. Rolling was on modern ball-rolling mill 60- 120. The rolls were manufactured at 5-coordinate machining center NORMA L-45, and geometric parameters were controlling on FAROARM measuring machine. Results. Following limit of geometric accuracy were identified: the limit due to manufacturing quality of deformation tool, the limit in setting ball-rolling mill and the measurement limit. Total limit was calculated under for all sizes of obtained balls. The table with gradation of grinding balls into two groups: ordinary accuracy and high accuracy, indicating maximum deviations in size was compiled. Conclusions. The study confirms that at now it is possible to obtain increased accuracy balls, which, due to decrease in stress concentration, will be minimally subject to destruction during hardening and external influences.